2017
DOI: 10.1902/jop.2016.160441
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on the Genetic Background of an Active Matrix Metalloproteinase‐8 Test in Finnish Adolescents

Abstract: Genetic polymorphisms of MMP3 and VDR are linked to initial periodontitis in Finnish adolescents, and the aMMP-8 chairside test can eventually detect initial periodontitis in young patients with predisposing genetic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 28 publications
(54 reference statements)
5
60
0
Order By: Relevance
“…Additionally, it identifies genetically predisposed adolescents [73]. A positive aMMP-8 test is based on a cutoff of 25 ng aMMMp-8 per milliliter of filtrate derived from 5 mL mouth rinse.…”
Section: Development Of Point Of Care/chairside Test For Oral (Permentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it identifies genetically predisposed adolescents [73]. A positive aMMP-8 test is based on a cutoff of 25 ng aMMMp-8 per milliliter of filtrate derived from 5 mL mouth rinse.…”
Section: Development Of Point Of Care/chairside Test For Oral (Permentioning
confidence: 99%
“…The test has been independently and internationally successful validated in Africa, Europe and USA, and in all studies it found to excellently differentiate periodontal health and disease [71,73,74,75,76]. …”
Section: Development Of Point Of Care/chairside Test For Oral (Permentioning
confidence: 99%
“…Indeed, a quantitative POC activated MMP8 (aMMP8) oral fluid test has been repeatedly and independently validated in Finland, Germany, Nigeria, Turkey, the Netherlands and the United States to successfully screen susceptible sites and patients, differentiate active and inactive perio dontal sites, predict the future disease progression and monitor treatment response and mainten ance therapy [3][4][5][6][7][8] , with a diagnostic sensitivity and specificity of 76-83% and 96%, respectively, and a turnaround time of 5-7 minutes. Furthermore, the test can identify initial periodontitis in genetically predisposed adolescents 5 .…”
mentioning
confidence: 99%
“…Furthermore, the test can identify initial periodontitis in genetically predisposed adolescents 5 . Thus, the aMMP8 test is effective in both adolescent and adult populations 3,4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation